2017
DOI: 10.24059/olj.v21i1.810
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Smile Sheets: A Case Study on the Evaluation and Iterative Improvement of an Online Faculty Development Program

Abstract: Institutions of higher education are struggling to meet the growing demand for online courses and programs, partly because many faculty lack experience teaching online. The eCampus Quality Instruction Program (eQIP) is an online faculty development program developed to train faculty to design and teach fully online courses. The purpose of this article is to describe the eQIP (one institution's multipronged approach to online faculty development), with a specific focus on how the overall success of the program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The results also complement the findings of Kahn and Pred (2002) and provide further evidence that mastery of new technology also impacts faculty satisfaction and helps to soften faculty attitudes about its use in instruction. These results are also consistent with studies by Chen et al (2017) and Buckenmeyer (2008) that providing readily available hands-on support factor into more acceptance and use of online technologies for instruction. While faculty may be skeptical about new technologies or new teaching methods, active participation with these technologies or formats may positively impact faculty attiutudes and perceptions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results also complement the findings of Kahn and Pred (2002) and provide further evidence that mastery of new technology also impacts faculty satisfaction and helps to soften faculty attitudes about its use in instruction. These results are also consistent with studies by Chen et al (2017) and Buckenmeyer (2008) that providing readily available hands-on support factor into more acceptance and use of online technologies for instruction. While faculty may be skeptical about new technologies or new teaching methods, active participation with these technologies or formats may positively impact faculty attiutudes and perceptions.…”
Section: Discussionsupporting
confidence: 90%
“…This notion of participation is consistent with the findings of Kahn and Pred (2002) who reported that carefully designed hands-on faculty workshops-that included mastery of software, adaptating technology for specific disciplines, website design, and electronically mediated course delivery-led to faculty satisfaction with the workshops, as well as attitudinal and usage changes. Similarly, Buckenmeyer (2009) and Chen et al (2017) found that if certain conditions exist, notably professional development and continuous access to resources, university faculty were more likely to accept and use appropriate technologies in significant instructional ways. Taken together, these studies suggest that faculty attitudes about the use of technology for teaching/learning are open to positive change if steps are taken to provide a technologyrobust infastructure and continuous technical hands-on support.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the traditional face-to-face environment, faculty can expect to succeed by relying on their mastery of the subject and their mastery of how to teach it. In an online environment, however, faculty face a further challenge: they also need to master how to teach in that special context (Chen, Lowenthal, Bauer, Heaps, & Nielsen, 2017; Gay, 2016; Rohland-Heinrich, 2016; Wingo et al, 2017). Online environments require faculty to master the particular pedagogical opportunities and constraints of a new medium.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Training is starting to be recognized as an important element in preparing faculty to meet the challenges of online teaching (Allison, 2015; Almarashdeh, Sahari, Zin, & Alsmadi, 2011; Bolliger et al, 2014; Chen et al, 2017; Guan & Stanford, 2016; Ling, 2014; Masoumi, 2010; OLC, 2017; Rohland-Heinrich, 2016; Terblanché, 2015). Training has been identified as a predictor of success in online teaching (Al-Busaidi, 2012), but the link between training and faculty satisfaction in the online environment deserves further exploration (Almarashdeh, 2016; Hoekstra, 2014; Wingo et al, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Another limitation was that the participants were volunteers for the professional development activity. According to Chen, Lowenthal, Bauer, Heaps, and Nielsen (2017), participants view professional development with higher satisfaction when it is not required. Finally, while efforts were made to situate the expert leaders and researcher as colleagues, participants may have felt compelled to overstate their satisfaction to appease organizational expectations.…”
Section: Discussionmentioning
confidence: 99%